A Process Integration Approach for Supply Chain Development - Lam, H.; Ng, Wendy (Woodhead Publishing Limited, 2013)
This chapter extends the application of the Process Integration (PI) approach to supply chains, especially developing further the analogy between Pinch Analysis and the field of operational research. The first part of this chapter introduces supply chains and supply chain performance measurement. In the following parts, the chapter provides clear insight into how the PI concept brings a significant contribution to the development of supply chain design. This novel approach, Pinch Analysis for the supply chain, will be presented. After an overview of the approach, case studies are outlined for purposes of demonstration.